2010
DOI: 10.1002/ca.21080
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic angiography in the gross anatomy dissection laboratory: Visualizing the aortic arch and its branches in a cadaver

Abstract: We present fluoroscopic images of the aortic arch and its branches obtained in a first year medical gross anatomy teaching laboratory after an aberrant right subclavian artery was discovered during dissection. The aortic arch and its branches in the cadaver were filled with contrast medium in molten agar. After the agar solidified, a portable fluoroscope was used to obtain radiographic images. These post-mortem images were then compared with computed tomography images obtained while the individual was living. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Without an opportunity to dissect a human body, we would have never learned about this variation in so much depth, nor would we have had the opportunity to experience the process of anatomical research. Our study and that of Vogt et al (2011) provide novel examples of how valuable clinically-relevant cadaveric dissection is in medical education.…”
Section: Embryology and Molecular Geneticsmentioning
confidence: 93%
See 2 more Smart Citations
“…Without an opportunity to dissect a human body, we would have never learned about this variation in so much depth, nor would we have had the opportunity to experience the process of anatomical research. Our study and that of Vogt et al (2011) provide novel examples of how valuable clinically-relevant cadaveric dissection is in medical education.…”
Section: Embryology and Molecular Geneticsmentioning
confidence: 93%
“…Although the presence of an ARSA has been well documented in the literature (Atay et al, 2006;Bednarkiewicz et al, 2003;Chaoui et al, 2005;Easterbrook, 1992;Inman et al, 2008;Kim et al, 2009;Ramaswamy et al, 2008;Simek et al, 2008;Tubbs et al, 2004;), few studies have described how finding one can be used as an educational strategy to facilitate learning in medical students. Recently, Vogt et al (2011) eloquently described how a group of medical students discovered an ARSA, used a fluoroscope to obtain images of the variant, and then correlated the images with computed tomography scans of the chest that were taken during the cadaver's life. The ingenuity of this study was that it demonstrated to the students how difficult it can be to recognize a variant with modern diagnostic imaging (Vogt et al, 2011).…”
Section: Embryology and Molecular Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…
We thank Dr. Muresian (2011) for his complimentary critique of our article (Vogt et al, 2011) and his comments that extend the discussion of this anatomical variation. He emphasizes the fact that an aberrant right subclavian artery does not have a singular appearance in all individuals but rather can have a range of diameters, a variety of courses, and an appearance that can change over time, as in the evolving pathology of atherosclerosis.
…”
mentioning
confidence: 95%
“…The article by Vogt et al (2011) offers to the reader some important aspects and details, which warrant particular consideration.…”
mentioning
confidence: 99%